PEMAHAMAN PESERTA DIDIK TENTANG PEMILIHAN PEMINATAN DALAM KURIKULUM 2013 DI KELAS X SMA SEMEN PADANG - -, Yomalisa - (Bimbingan dan Konseling, 2014)
Curriculum implementation in 2013 will be able to pose a problem for senior high schoollearners on a swordfish capable in their choice of subjects specialization group, so it can bedifficult and a tendency to fail in learning. The purpose of this study is to describe the learnersunderstanding of the selection of specialization in the curriculum in 2013. Type of research used inthis study was descriptive quantitative research. That is, this study to gather information on thestatus of an existing symptoms, that is the state of symptoms according to what it is at time of thestudy. Total population in this study is 219 learners. The research techniques used randomsampling is a sampling technique that is done by taking a random representative of each grade often in padang cement senior high school. Total sampling 0f 46 learners. The disclosure tool used inthis study is a questionnaire. Subsequent data analysis techniques used namely the interpretation ofdata with a range of classification. Result of the findings of this study illustrate how the learnersunderstanding of the selection of specialization in curriculum 2013 in the ten grade padang cementsenior high school, thus it can be concluded that the selection of studens understanding ofcurriculum 2013 selection in general the bulk of the studens are on familiar criteria.